(untitled) (Applied Biological Research, 2013)
The effect of various orchard floor management treatments of young cherry trees (Prunus avium L) cv. Bigarreau Noir Gross (Misri) on growth, yield, quality and leaf mineral element concentrations were investigated during the year 2008 and 2009 at Ambri Research Station, Pahnoo, Shopian SKUAST-K Shalimar. The treatments included growing of kharif- and rabi-sown intercrops viz., maize, pea, strawberry, cabbage, red clover, french bean and oats along with a control (clean cultivation). The results revealed that young cherry trees intercropped with leguminous crops (pea, red clover or french bean) performed better with respect to growth, yield, quality and leaf mineral element concentration than control or intercropping with heavy feeder crops (strawberry, cabbage, oats or maize). Higher produce and heavier fruit was obtained from the cherry trees intercropped with pea followed by red clover and french bean. The firmness, colour and ascorbic acid content were high in fruits from cherry trees intercropped with red clover or French bean.